Exosomes in breast cancer management: Where do we stand? A literature review. (3rd February 2022) - Triantafyllou, Alexandra; Gazouli, Maria; Theodoropoulos, Charalampos; Zografos, Eleni; Zografos, George C.; Michalopoulos, Nikolaos V.
Abstract: Background: Exosomes constitute cellular molecular fingertips that participate in intercellular communication both in health and disease states. Hence, exosomes emerge as critical mediators of cancer development and progression, as well as potential biomarkers and novel therapeutic targets. Objective: To review literature data regarding applications of circulating exosomes in breast cancer management. Methods: This is a literature review of relevant published studies until April 2020 in PubMed and Google Scholar databases. Original papers in the English language concerning exosome related studies were included. Results: Exosomes represent molecular miniatures of their parent cells. Several homeostatic mechanisms control exosomal secretion and synthesis. Exosomal exchange among cells creates an intricate intercellular crosstalk orchestrating almost every tissue process, as well as carcinogenesis. Available data highlight exosomes as major mediators of cancer development and progression. The secretion of specific exosomal molecules, particularly miRNAs, correlates with the underlying processes and can be used as a means of tumor detection and prognostic assessment. Conclusions: Exosomal miRNAs expression profiles and levels closely relate to cancer extent, type and prognosis. Deep comprehension of such correlations and systematization of experimental outcomes will offer a novel approach in cancer detection and management.